An in vitro investigation of the anti-inflammatory and immunosuppressive effects of the synthetic contraceptives medroxyprogesterone acetate (MPA) and norethisterone acetate (NET-A) - Kriek, W. J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Pathology. Medical Microbiology))--University of Stellenbosch, 2005.